Dual role of Mpl receptor during the establishment of definitive hematopoiesis - Petit-Cocault, Laurence; Volle-Challier, Cécile; Fleury, Maud; Péault, Bruno; Souyri, Michèle (Development (Cambridge), 2007)
Cytokine signaling pathways are important in promoting hematopoietic stem cell (HSC) self-renewal, proliferation and differentiation. Mpl receptor and its ligand, TPO, have been shown to play an essential role in the early steps of adult hematopoiesis. We previously demonstrated that the cytoplasmic domain of Mpl promotes hematopoietic commitment of embryonic stem cells in vitro, and postulated that Mpl could be important in the establishment of definitive hematopoiesis. To answer this question, we investigated the temporal expression of Mpl during mouse development by in situ hybridization. We found Mpl expression in the HSCs clusters emerging in the AGM region, and in the fetal liver (FL) as early as E10.5. Using Mpl -/- mice, the functional relevance of Mpl expression was tested by comparing the hematopoietic progenitor (HP) content, long-term hematopoietic reconstitution (LTR) abilities and HSC content of control and Mpl -/- embryos at different times of development. In the AGM, we observed delayed production of HSCs endowed with normal LTR but presenting a self-renewal defect. During FL development, we detected a decrease in HP and HSC potential associated with a defect in amplification and self-renewal/survival of the lin - AA4.1 + Sca1 + population of HSCs. These results underline the dual role of Mpl in the generation and expansion of HSCs during establishment of definitive hematopoiesis.